Joint associations of sleep duration and insomnia symptoms with subsequent sickness absence: The Helsinki Health Study. Issue 5 (July 2013) - Lallukka, Tea; Haaramo, Peija; Rahkonen, Ossi; Sivertsen, Børge
Aims : We aimed to examine the joint associations of sleep duration and insomnia symptoms with subsequent sickness absence of various lengths while considering several covariates. Methods : Baseline surveys among 40–60-year-old employees of the City of Helsinki, Finland, ( N = 6535) were prospectively linked with employer's personnel register data comprising short self-certified (1–3 days), medically-certified intermediate (4–14 days) and long (15 days or more) sickness absence spells. Average follow-up time was 4.1 years. Sleep duration, insomnia symptoms, sociodemographics, working conditions, health behaviours and health were self-reported in the surveys. Poisson regression analysis was used. Results : Insomnia symptoms were associated with sickness absence at all levels of sleep duration. Adjusting for gender and age, U-shaped associations regarding sleep hours were found. Thus, those reporting short or long sleep and reporting insomnia symptoms had a higher risk for medically-certified intermediate and long sickness absence as compared to those reporting 7 hours of sleep without insomnia symptoms. Also, those reporting 6, 7, and 8 hours of sleep had a higher risk for such sickness absence, if they reported insomnia. Weak associations were also found for self-certified sickness absence, and for those reporting short and long sleep without insomnia. Adjustments attenuated the associations, but they mainly remained. Conclusions : These results suggest primacy of the effects of insomnia symptoms over sleep duration on sickness absence. Although insomnia dominated the joint association, U-shaped associations suggest that both sleep duration and insomnia symptoms need to be considered to promote work ability.